The effects of an 8-week complex training program on lower limb explosive power and movement agility in adolescent female badminton players - Hu, Rui; Zhao, Minchen; Shen, Xiang; Wang, Zhiming (Frontiers in Physiology, 2025)
BackgroundBadminton requires high-intensity lower limb explosive power and agility for executing rapid lunges, jumps, and directional changes. Complex training (CT) combines heavy resistance exercises with plyometric activities to enhance maximal strength and explosive performance through post-activation performance enhancement (PAPE). However, limited research exists on CT effects in adolescent female badminton players.ObjectiveTo investigate the effects of an 8-week complex training program on lower limb explosive power and movement agility in adolescent female badminton players.MethodsThirty-two adolescent female badminton players were randomly allocated into complex training group (CT group, n = 16, age: 15.69 ± 0.95 years) and resistance training group (RT group, n = 16, age: 15.63 ± 1.15 years). The CT group performed resistance exercises (75%–85% 1RM) paired with plyometric exercises twice weekly for 8 weeks, while the RT group completed traditional resistance training with the same frequency. Pre- and post-intervention assessments included squat jump (SJ), countermovement jump (CMJ), bilateral and unilateral jumps, sprint tests (5 m, 10 m, 15 m, 20 m), hexagon test, modified 505 change of direction (COD) test, on-court COD test, and isometric mid-thigh pull (IMTP). Two-way repeated measures ANOVA was used for statistical analysis (p < 0.05).ResultsSignificant group × time interactions were observed for SJ, CMJ, unilateral jumps, sprint performance (5 m, 10 m, 20 m), and agility tests (all p < 0.05). The CT group showed greater improvements compared to RT group: SJ (1.83 cm vs. 0.95 cm, Cohen’s d = 1.196 vs. 0.642), CMJ (3.64 cm vs. 1.27 cm, Cohen’s d = 1.949 vs. 0.681), 5 m sprint (0.18s vs. 0.06s improvement, Cohen’s d = 1.889 vs. 0.667), hexagon test (1.29s vs. 0.03s improvement), and COD performance. Both groups significantly improved IMTP with no between-group differences (p > 0.05).ConclusionAn 8-week complex training program elicited significantly greater improvements in lower limb explosive power, sprint acceleration, and multidirectional agility compared to traditional resistance training in adolescent female badminton players. These findings suggest CT is an effective, sport-specific training intervention that capitalizes on the heightened neuromuscular plasticity of adolescent athletes.